Unveiling liquid-phase exfoliation of graphite and boronnitride using fluorescent dyes through combinedexperiments and simulations - He, Yilin (2024)
Liquid-phase exfoliation (LPE) in aqueous solutions provides a simple, scalable, and green approach to produce 2D materials. By combining atomistic simulations with exfoliation experiments, the interaction between a surfactant and a 2D layer at the molecular scale can be better understood. In this work, two different dyes, corresponding to rhodamine B base (Rbb) and to a phenylboronic acid BODIPY (PBA-BODIPY) derivative, are employed as dispersants to exfoliate graphene and hexagonal boron nitride (hBN) through sonication-assisted LPE. The exfoliated 2D sheets, mostly as few-layers, exhibit good quality and high loading of dyes. Using molecular dynamics (MD) simulations, the binding free energies are calculated and the arrangement of both dyes on the layers are predicted. It has been found that the dyes show a higher affinity toward hBN than graphene, which is consistent with the higher yields of exfoliated hBN. Furthermore, it is demonstrated that the adsorption behavior of Rbb molecules on graphene and hBN is quite different compared to PBA-BODIPY.